No survival benefit could be obtained from adjuvant radiotherapy in esophageal cancer treated with neoadjuvant chemotherapy followed by surgery: A SEER-based analysis - Zheng, Si-Yue; Qi, Wei-Xiang; Zhao, Sheng-Guang; Chen, Jia-Yi (Frontiers in Oncology, 2022)
Background The aim of this study is to assess the clinical benefit of postoperative radiotherapy (PORT) in patients with esophageal cancer (EC) who treated with neoadjuvant chemotherapy (NAC) and surgery via a national population-based database. Methods Patients diagnosed with EC between 2004 and 2015 were identified from the Surveillance, Epidemiology, and End Results (SEER) database. Kaplan–Meier survival analysis was used to compare the overall survival (OS) and cause-specific survival (CSS) difference between PORT vs. no-radiotherapy (RT) groups before and after propensity score matching (PSM). After PSM for baseline characteristics, Cox proportional hazard regression was performed to investigate the factors associated with OS. Results A total of 321 patients were included in the analysis. Of them, 91 patients (28%) received PORT. In the unmatched population, the no-RT group had improved OS compared with PORT (44 vs. 25 months, p = 0.002), and CSS was similar in patients undergoing NAC with or without PORT (42 vs. 71 months, p = 0.17). After PSM for baseline characteristics, the OS benefit of the no-RT group over the PORT group remained significant with a median OS of 46 vs. 27 months (p = 0.02), and CSS remained comparable between groups (83 vs. 81 months, p = 0.49). In subgroup analyses, PORT did not improve the OS among patients with adenocarcinoma in the subgroups of cN0, cN1, and cN2–3 (all p > 0.05). In Cox regression, aged ≥71 years old, cT3–4, cN2–3, and receiving PORT were independent predictors of worse OS, whereas cT4 and cN2–3 were independent predictors of worse CSS (all p < 0.05). Conclusions The present study demonstrated that no survival benefit could be obtained from the additional use of PORT after NAC and surgery in patients with EC. Well-designed prospective trials are needed to confirm our findings.